2020
DOI: 10.1002/pds.5166
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of risk minimisation measures for valproate: A drug utilisation study in Europe

Abstract: Purpose The purpose of this study was to evaluate the effectiveness of the risk minimisation measures (RMMs) implemented in Europe in 2014 for valproate‐containing products to mitigate their risk during pregnancy and to characterise valproate prescribing patterns in women of childbearing potential (WCBP) before and after implementation of RMMs. Methods A multinational cohort study based on existing data sources using a pre‐/post‐ design was performed in five European countries (France, Germany, Spain, Sweden, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…29 In addition, a recent drug utilisation study examined valproate prescribing patterns in five European countries (France, Germany, Spain, Sweden and the UK) and found that, in all countries, the proportion of WCBP prescribed valproate had decreased (between 30.1% and 52.3%) following the 2014 intervention. 30 Similarly, our study identified an overall decline in the month-to-month use of valproate among WCBP (16-44 years) following the 2014 EMA intervention.…”
Section: Comparison With Previous Studiessupporting
confidence: 57%
See 1 more Smart Citation
“…29 In addition, a recent drug utilisation study examined valproate prescribing patterns in five European countries (France, Germany, Spain, Sweden and the UK) and found that, in all countries, the proportion of WCBP prescribed valproate had decreased (between 30.1% and 52.3%) following the 2014 intervention. 30 Similarly, our study identified an overall decline in the month-to-month use of valproate among WCBP (16-44 years) following the 2014 EMA intervention.…”
Section: Comparison With Previous Studiessupporting
confidence: 57%
“…These patterns observed, support our recent survey study findings from the Irish HCP setting, which found that all responding neurologists reported that they had considered an alternative treatment before initiating their patient on valproate 29 . In addition, a recent drug utilisation study examined valproate prescribing patterns in five European countries (France, Germany, Spain, Sweden and the UK) and found that, in all countries, the proportion of WCBP prescribed valproate had decreased (between 30.1% and 52.3%) following the 2014 intervention 30 . Similarly, our study identified an overall decline in the month‐to‐month use of valproate among WCBP (16–44 years) following the 2014 EMA intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these positive trends, there are studies supporting our impression that the use of alternative drugs before valproate initiation is still suboptimal in Germany. A study assessing the proportion of women with newly diagnosed epilepsy using valproate as second-line rather than first-line therapy in various European countries--before and after implementation of risk minimization measures--did not observe a change in Germany, while the proportion increased in Sweden, the UK, and Spain (Toussi et al, 2021b). The same study also investigated changes in the incidence of valproate-exposed pregnancies, but for this part of the analysis, no data from Germany were available.…”
Section: Discussionmentioning
confidence: 97%
“…On these grounds, the European Medical Association introduced extra measures to enforce the previous restrictions. Further studies are underway to determine the effectiveness of the new measures and to monitor valproate use in women with childbearing potential and pregnancies exposed to it [36].…”
Section: Questions That the Patient Often Posesmentioning
confidence: 99%